(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
This paper analyzes the impact of voluntary private certifications, focusing on GlobalGAP, on the performance of non-traditional agroexports in Peru. The main objective is to determine whether holding these certifications enhances the export value of Peruvian firms. The central hypothesis is that voluntary private certifications are positively correlated with a higher export value. The theoretical model examines the relationship between the determinants for obtaining the GlobalGAP certification and its benefits, assessing the percentage variation in the export value of companies in dollars. The analysis employs the propensity score matching (PSM) model and a difference-in-differences (DID) estimator to evaluate the effect on export value between certified and non-certified companies. The results show that while GlobalGAP certification positively contributes to export value, this effect does not extend to microenterprises. The paper provides new empirical evidence to the literature in Peru, offering data that can be used to design public policies. The findings support the promotion of certifications in the agro-export sector, fostering Peruvian agroexports in the international market and strengthening the competitiveness of local agricultural activities.